2017
DOI: 10.1523/jneurosci.3537-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Memory Reactivation during Sleep Adaptively Promotes the Strengthening or Weakening of Overlapping Memories

Abstract: System memory consolidation is conceptualized as an active process whereby newly encoded memory representations are strengthened through selective memory reactivation during sleep. However, our learning experience is highly overlapping in content (i.e., shares common elements), and memories of these events are organized in an intricate network of overlapping associated events. It remains to be explored whether and how selective memory reactivation during sleep has an impact on these overlapping memories acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 60 publications
7
76
0
Order By: Relevance
“…However, the changes were more significant in the experiments with sensory cue stimulation (Fig. 2f, right) where the greater amount of slow oscillations was found to be elicited with the targeted sound compared to the experiments with a control new sound (Oyarzun et al, 2017). To examine whether the enhanced performance in our simulations was merely due to the higher Up state count, we reduced the sleep duration from 300s to 260s for the cued sleep to obtain comparable Up state count to the uncued sleep.…”
Section: Open-loop Periodic Stimulation During Sleep Enhances Memory mentioning
confidence: 88%
See 2 more Smart Citations
“…However, the changes were more significant in the experiments with sensory cue stimulation (Fig. 2f, right) where the greater amount of slow oscillations was found to be elicited with the targeted sound compared to the experiments with a control new sound (Oyarzun et al, 2017). To examine whether the enhanced performance in our simulations was merely due to the higher Up state count, we reduced the sleep duration from 300s to 260s for the cued sleep to obtain comparable Up state count to the uncued sleep.…”
Section: Open-loop Periodic Stimulation During Sleep Enhances Memory mentioning
confidence: 88%
“…presumably enhance reactivation of the relevant neuronal representations that improves memory consolidation. TMR was shown to improve both hippocampus-independent procedural memories (Antony et al, 2012;Schonauer, Geisler and Gais, 2014;Cousins et al, 2014;Cousins et al, 2016) and hippocampus-dependent declarative memories (Rudoy et al, 2009;Rasch et al, 2007;Batterink, Creery and Paller, 2016;Oyarzun et al, 2017). In one experiment, an odor was associated with learning a spatial card location task; subsequent presentation of the odor cue during sleep led to selective enhancement of this memory compared to the sleep without cueing (Rasch et al, 2007).…”
Section: The Mechanisms Of Strengthening Memories By Stimulation Durimentioning
confidence: 99%
See 1 more Smart Citation
“…6 Hz) and spindle band (ca. 13 Hz) (Groch, Schreiner, Rasch, Huber, & Wilhelm, 2016;Lehmann, Schreiner, Seifritz, & Rasch, 2016;Oyarzún, Morís, Luque, de Diego-Balaguer, & Fuentemilla, 2017;Schreiner, Lehmann, & Rasch, 2015). According to our working model, increase in the theta band might reflect successful reinstatement of memory traces by cueing during sleep, whereas increased activity in the spindle band relates to processes of integration and stabilization of memories after reinstatement of the memory trace by the cue ).…”
Section: Abstract: Reactivation; Aging; Vocabulary Learning; Memory Cmentioning
confidence: 87%
“…The authors suggested that the stimulation of some low‐value items could have led to a generalized reactivation for the whole category of low‐value items. More recently, Oyarzún and colleagues used the same visuospatial location task to test the effect of TMR on overlapping memories. Specifically, participants had to initially learn the location of 15 card‐pairs (set X1–X2) and after 5 min (contiguous condition) or 3 h (delayed condition), they were asked to encode the location of a second set of 15 card‐pairs (set X1–X3).…”
Section: Tmr and Declarative Memorymentioning
confidence: 99%